A review of the lesser mealworm beetle (Alphitobius diaperinus) as a reservoir for poultry bacterial pathogens and antimicrobial resistance. Issue 1 (2nd January 2022) - Smith, Rachel; Hauck, Ruediger; Macklin, Kenneth; Price, Stuart; Dormitorio, Teresa; Wang, Chengming
SUMMARY: The lesser mealworm beetle ( Alphitobius diaperinus ) is one of the most abundant and resilient insect pests within poultry houses and has been observed dwelling in all types of poultry operations. The beetle is a nuisance and causes structural damage to poultry houses, which is costly for producers. Most importantly, it has been demonstrated that the lesser mealworm beetle is capable of carrying a wide variety of poultry-specific and zoonotic viral, bacterial, and parasitic pathogens. This article will focus on investigating the lesser mealworm beetle's role in the retention and transmission of bacterial pathogens and its contribution to the development and dissemination of antimicrobial resistance (AMR). Field and laboratory studies conducted to investigate the relationship between the lesser mealworm beetle and poultry-associated bacterial pathogens will be reviewed to summarise the current understanding of the beetle's contribution to bacterial pathogen transmission and antimicrobial resistance, and to provide a foundation for future studies.